Determination of the seismic moment tensor for local events in the South Shetland Islands and Bransfield Strait. - GUIDARELLI, MARIANGELA; PANZA, GIULIANO (Geophysical Journal International, 2006)
Six events with magnitude between 3 and 5.6 have been analysed based on regional waveforms recorded by the temporal Seismic Experiment in Patagonia and Antarctica seismic broad-band network in the Bransfield Strait and the South Shetland Islands in the period 1997–1998. The source parameters have been retrieved using a robust methodology (INDirect PARametrization) to stabilize the inversion of a limited number of noisy records. This methodology is particularly important in oceanic environments, where the presence of seismic noise and the small number of stations makes it difficult to analyse small magnitude events. The source mechanisms obtained are quite variable but consistent with the active tectonic processes and the complicated structure of the South Shetland Island region.